2011
DOI: 10.1063/1.3672214
|View full text |Cite
|
Sign up to set email alerts
|

On-chip single photon emission from an integrated semiconductor quantum dot into a photonic crystal waveguide

Abstract: We demonstrate the in-plane emission of highly-polarized single photons from an InAs quantum dot embedded into a photonic crystal waveguide. The spontaneous emission rates are Purcell-enhanced by the coupling of the quantum dot to a slowlight mode of the waveguide. Photon-correlation measurements confirm the sub-Poissonian statistics of the in-plane emission. Under optical pulse excitation, single photon emission rates of up to 19 MHz into the guided mode are demonstrated, which corresponds to a device efficie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
85
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 23 publications
0
85
0
Order By: Relevance
“…Nowadays, state-of-the-art photonic crystal waveguides offer close to unity b-factors. [2][3][4] However, the large transmission losses of this waveguide technology 5 prevents a straightforward scaling up to large photonic chips. One way to get around this difficulty is to couple a short photonic crystal section to a ridge waveguide, 6 which features excellent optical transmission.…”
mentioning
confidence: 99%
“…Nowadays, state-of-the-art photonic crystal waveguides offer close to unity b-factors. [2][3][4] However, the large transmission losses of this waveguide technology 5 prevents a straightforward scaling up to large photonic chips. One way to get around this difficulty is to couple a short photonic crystal section to a ridge waveguide, 6 which features excellent optical transmission.…”
mentioning
confidence: 99%
“…It is difficult to precisely determine the efficiency of the out-coupling grating but the detected count rates in this case are comparable to previous reports where the in-plane emission was collected directly from the exit of the waveguide. 23,29 Calculations of the photonic band structure of an infinite PCWG using the plane-wave expansion method with the same parameters as the one used in the experiment show spectral matching of the emission at 895.1 nm with the fundamental y-polarized propagating mode. 29 Fig .…”
Section: (B) a Tunable Continuous Wave (Cw) Laser Polarized Along Thmentioning
confidence: 99%
“…However, in the emerging field of photonic quantum information technology, it is highly desirable for the integrated quantum emitter to be able to emit highly indistinguishable photons into an on-chip quantum circuit. The integration of QDs in photonic circuits, in particular photonic crystal waveguides (PCWGs), [21][22][23][24][25][26][27] has extended the use of these emitters as integrated in-plane quantum light sources. These systems offer broadband operation, 20 efficiency 23,28 and scalability.…”
mentioning
confidence: 99%
“…Recent studies have reported the integration of QDs in photonic circuits, in particular photonic crystal waveguides, [16][17][18][19][20][21] which extended the use of these emitters as integrated in-plane quantum light sources.…”
mentioning
confidence: 99%